2011
DOI: 10.1260/0263-0923.30.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Whole-Body Vibration Related Health Problems in Occupational Medicine

Abstract: Occupational whole-body vibration (WBV) exposed workers may report nonspecific health complaints or debilitating physical disorders. Health care providers and safety professionals may not recognize such occupational injuries and be unfamiliar with appropriate exposure assessment. Method: Review of peer-reviewed clinical studies and publications, medical evidence, differential diagnostic evaluation protocols, surveillance programs, national and international standards, and intervention recommendations regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Although it is recognised there is potentially a relationship between performance decrements and injury risk, the notion of injury is not discussed herein. Such relationships are discussed comprehensively in other reviews (Bovenzi 2006;Johanning 2011;Kittasumy and Buchholz 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although it is recognised there is potentially a relationship between performance decrements and injury risk, the notion of injury is not discussed herein. Such relationships are discussed comprehensively in other reviews (Bovenzi 2006;Johanning 2011;Kittasumy and Buchholz 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Where physical responses are considered, such as hand-eye coordination, muscle reflex and heart response, much has been written on the acute responses to human function during and following WBV (Mani et al 2010;McLeod and Griffin 1989;Shoenberger 1972). Frequently, it has been recognised that vibration in the workplace, particularly workplaces that require vehicle transit, is sufficient to induce a physical response in humans (Johanning 2011;Kittasumy and Buchholz 2004;Milosavljevic et al 2011). In some cases, alteration to human function may have negative implications for physical performance in job tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], it was shown that if the exposure to low-frequency vibrations produced by commercial vehicles were more than 8 hours every day, conventional vehicle seating with passive suspension could not protect the driver's body from the effects of WBVs. According to a medical research report by Johanning (2011) [6], low-frequency vibrations may cause resonances of human organs and tissues. There, it was claimed that back pain disease is one of the most common occupational injuries because the lower back of the human body is sensitive to low-frequency vibrations of 4-10 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…2019, 9, In terms of seat vibration isolation measurements, Mozaffarin et al (2008) [10] designed an active dummy technique (Figure 2), which adopted lateral and longitudinal actuators to produce forces in the vertical and lateral directions, respectively, to simulate the dynamic response of three different human body masses by reproducing the equivalent dynamic mass. [6].…”
Section: Introductionmentioning
confidence: 99%
“…WBV is associated with an increased risk of low back pain (LBP) when operators are exposed to vibrations while in a sitting posture (Johanning, 2011;Lis et al, 2007). More than 25% of employees are affected by LBP each year (Lee et al, 2001).…”
mentioning
confidence: 99%